Sukapura Go Digital: Pemberdayaan UMKM, Kelompok Tani, dan Pelaku Wisata Melalui Pelatihan Digital Marketing dan Konten Kreatif di Desa Ngepung, Kec.Sukapura Kabupaten Probolinggo - Mohammad Rofiuddin (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2026)
Sukapura Village, Probolinggo Regency, holds significant economic potential as a buffer zone for Mount Bromo tourism; however, this potential remains underutilized due to low digital literacy among residents, weak UMKM product branding, and the lack of integration between the agricultural, micro-enterprise, and tourism sectors in a digital economic chain. The community service program "Sukapura Go Digital" was designed to address these challenges through a participatory approach combining training and mentoring activities. The program was implemented in September 2025 at Masjid Barakah, Ngepung Village, Sukapura, involving 38 participants from three target groups: 17 UMKM actors, 14 farmer group members, and 7 tourism agents/guides. Implementation methods included interactive lectures, demonstrations, hands-on practice, personal mentoring, and evaluation. Results indicate that 84% of participants were able to upload content on Instagram, 79% mastered WhatsApp Business features, and 73% understood basic digital branding concepts. The program successfully facilitated the creation of 22 business Instagram accounts, 15 WhatsApp Business accounts, 7 business locations on Google Maps, and 5 marketplace accounts. Cross-sector collaboration also began to emerge, evidenced by supply partnerships between farmers and UMKM actors, as well as the promotion of local products by tourism agents. This program demonstrates that community-based village digitalization can serve as an effective strategy for strengthening local economies and building a sustainable connected economic ecosystem.